8.4k views
2 votes
Which choice is equivalent to the product below when x≥x​

Which choice is equivalent to the product below when x≥x​-example-1

2 Answers

4 votes

Answer:

B

Explanation:

Using the rule of radicals


√(a) ×
√(b)
√(ab)

Given


√(6x^2) ×
√(3x)

=
√(18x^3)

=
√(9(2)x^2(x))

=
√(9) ×
√(2) ×
√(x^2) ×
√(x)

= 3 ×
√(2) × x ×
√(x)

= 3x ×
√(2) ×
√(x)

= 3x
√(2x) → B

User Patrick Allen
by
5.2k points
3 votes

Answer:

B.

Explanation:

If you dont understand what I wrote, just ask!

Which choice is equivalent to the product below when x≥x​-example-1
User Marko Taht
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.